2019
DOI: 10.1016/j.mrrev.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of epigenetic modifiers in repair of DNA damage associated with chronic inflammatory diseases

Abstract: At sites of chronic inflammation epithelial cells are exposed to high levels of reactive oxygen species (ROS), which can contribute to the initiation and development of many different human cancers. Aberrant epigenetic alterations that cause transcriptional silencing of tumor suppressor genes are also implicated in many diseases associated with inflammation, including cancer. However, it is not clear how altered epigenetic gene silencing is initiated during chronic inflammation. The high level of ROS at sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 165 publications
(176 reference statements)
0
28
0
Order By: Relevance
“…Balance between proand anti-inflammatory mechanisms is responsible for tissue homeostasis (17). However, an abnormal imbalance is often associated with the development of cancer accompanied by an inflammatory response (18)(19)(20)(21). Inflammatory responses are mediated by specific cytokines and chemokines commonly expressed by immune cells; however, cancer cells have also been reported to produce cytokines and chemokines in order to promote tumorigenesis in an inflammatory microenvironment (22).…”
Section: Introductionmentioning
confidence: 99%
“…Balance between proand anti-inflammatory mechanisms is responsible for tissue homeostasis (17). However, an abnormal imbalance is often associated with the development of cancer accompanied by an inflammatory response (18)(19)(20)(21). Inflammatory responses are mediated by specific cytokines and chemokines commonly expressed by immune cells; however, cancer cells have also been reported to produce cytokines and chemokines in order to promote tumorigenesis in an inflammatory microenvironment (22).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that an expanded CTG repeat itself is responsible for induction of methylation 29 The connection between MSH2-induced repeat instability and upstream methylation may be indirect through a third partner. In an in vitro human model in which DNA double strand breaks (DSBs) were induced, it has been suggested that the MMR pathway recruits epigenetic modifiers such as the DNA methyl transferase DNMT1 at DNA damage sites in order to contribute to the DNA repair process [34][35][36] . After a successful repair, demethylase activity possibly restores the methylated site to its original unmethylated state 36 .…”
Section: Discussionmentioning
confidence: 99%
“…In an in vitro human model in which DNA double strand breaks (DSBs) were induced, it has been suggested that the MMR pathway recruits epigenetic modifiers such as the DNA methyl transferase DNMT1 at DNA damage sites in order to contribute to the DNA repair process [34][35][36] . After a successful repair, demethylase activity possibly restores the methylated site to its original unmethylated state 36 . In our MSH2WT hESC lines carrying a CTG expansion, CpG methylation flanking the CTG repeat is maintained and even increased over time in cell culture as in VUB19WT-SC1 and VUB19WT-SC2.…”
Section: Discussionmentioning
confidence: 99%
“…Once DNA repair proteins access DNA, “repressive” chromatin modifiers such as histone deacetylases (HDACs) are recruited to “close” the chromatin and repress transcriptional activity. Finally, chromatin is restored back to its original state when repair is completed (Ding et al, ). In response to oxidative DNA damage, we demonstrated that (1) JAK2 is recruited to chromatin, (2) JAK2 interacts with MSH2 and MSH6 in the nucleus, and (3) inhibiting JAK2 alters the chromatin interaction of MSH2, MSH6, DNMT1, and PRC2 members.…”
Section: Discussionmentioning
confidence: 99%